2021
DOI: 10.1182/bloodadvances.2020003217
|View full text |Cite
|
Sign up to set email alerts
|

G9a/GLP targeting in MM promotes autophagy-associated apoptosis and boosts proteasome inhibitor–mediated cell death

Abstract: Multiple myeloma (MM) is an (epi)genetic highly heterogeneous plasma cell malignancy that remains mostly incurable. Deregulated expression and/or genetic defects in epigenetic-modifying enzymes contribute to high-risk disease and MM progression. Overexpression of the histone methyltransferase G9a was reported in several cancers, including MM, correlating with disease progression, metastasis, and poor prognosis. However, the exact role of G9a and its interaction partner G9a-like protein (GLP) in MM biology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…Inhibition of p-p70, p-S6, p-4EBP1 and p-eIF4E has been show to impair MM progression and induce cell death [ 46 , 48 ]. For instance, our research group has previously shown that G9a/GLP targeting in myeloma inhibits p-mTOR, followed by a decrease in p-4EBP1 and p-eIF4E, leading to MM apoptosis [ 49 ]. However, the PRAS40-mediated protein synthesis pathway as a whole has not been studied yet in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of p-p70, p-S6, p-4EBP1 and p-eIF4E has been show to impair MM progression and induce cell death [ 46 , 48 ]. For instance, our research group has previously shown that G9a/GLP targeting in myeloma inhibits p-mTOR, followed by a decrease in p-4EBP1 and p-eIF4E, leading to MM apoptosis [ 49 ]. However, the PRAS40-mediated protein synthesis pathway as a whole has not been studied yet in MM.…”
Section: Discussionmentioning
confidence: 99%
“…This work could also shed light on combinatorial post-translational modi cation states involving these newly identi ed targets in vivo, as well as provide new insights into mechanisms of PTM cross-talk and how oncohistones can impart changes in the epigenome [42], [43]. More interestingly, in vivo perturbations in EHMT1/GLP and EHMT2/G9a have been implicated in many cellular processes including autophagy [44], DNA methylation, [35], [45], hypoxia [46], tumor suppression [47]- [50], chromatin remodeling [20], and synaptic plasticity [51] to name a few, and homozygous loss of EHMT1/GLP results in embryonic lethality in mice [52]. Additionally, both enzymes have been the focus of cancer therapies in recent years [48], [53]- [57].…”
Section: Discussionmentioning
confidence: 92%
“…More interestingly, in vivo perturbations in EHMT1/GLP and EHMT2/G9a have been implicated in many cellular processes including autophagy [ 43 ], DNA methylation, [ 35 , 44 ], hypoxia [ 45 ], tumor suppression [ 46 49 ], chromatin remodeling [ 20 ], and synaptic plasticity [ 50 ] to name a few, and homozygous loss of EHMT1/GLP results in embryonic lethality in mice [ 51 ]. Additionally, both enzymes have been the focus of cancer therapies in recent years [ 44 , 47 , 49 , 52 54 ].…”
Section: Discussionmentioning
confidence: 99%